TAMBAK LOROK AS "FISHERMAN VILLAGE" - Etika Sukma Adiyanti (International Conference on Coastal and Delta Areas, 2015)
Global warming causes climate change and sea level rise. This is a threat for coastalregions, especially for coastal settlements with activities that are influenced by this natural phenomenon. Consequences are damage of houses, humid house environment, sustainability of the houses, obstructed economic activities and domestic works, disruption of sanitation facilities, lack of electricity, failure of transport system, psychological issues and other. Icons Tambak Lorok as " Fisherman Village " is not something familiar to residents of the city of Semarang . Especially for the housewife who every day have to buy the ingredients high in protein and omega fish auction which is adjacent to the main street market in the village ofTambak Lorok. However, there are major problems that are being experienced by this small neighborhood . In fact, this issue includes seven infrastructure that should spoil the fishermen in activity with marine life . With this research we will investigate water urbanism and climate change resiliency in Semarang, specifically the traditional fishercommunity of Tambak Lorok. We intend to find out how the local people in the fisher settlement Tambak Lorok deal with water urbanism, proverty and living with floods.Keywords: Fishercommunity, Environment, Climate Change, Settlement